Performance Evaluation of a 2-kWp Grid Connected Photovoltaic System in Gate 3 Universiti Teknologi PETRONAS - WONG, SAMUEL WENG FAI (2018)
Energy demand of the world increases year by year. Renewable energy has become a good alternative energy source. Solar energy has attracted a great attention and consideration around the world especially in Malaysia. Malaysia is located in the equatorial region, which receives huge amount of sun radiation along the year, which enhances the performance of the photovoltaic system.